Indian endurance athletes` menstrual cycle: practices, knowledge, communication, health, and changes in perceptions across the phases - Majumder, T.; De Martin Topranin, V.; Sandbakk, Ø.; Noordhof, D. A. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To describe menstrual cycle (MC)-related practices, knowledge, communication, and health in Indian endurance athletes and to investigate the changes in their perception of sleep quality, readiness to train, training quality, fitness, and performance across the MC.